Prospective Study of Posterior Cervical Foraminotomy for Cervical Radiculopathy in Absenceof Myelopathy - Umesh D. Jain; Amol Gowaikar; Pradip Patil; Uday Ghate; Rishabh Nair (Journal of Orthopedics, Traumatology and Rehabilitation)
Objective: To determine clinical and patient satisfaction outcomes after posterior cervical foraminotomy (PCF), for the patients suffering from cervical monoradiculopathy, in the absence of myelopathy. To assess the efficacy of PCF. Methods: This was a prospective and multicentric study including patients of cervical monoradiculopathy, who underwent PCF surgery in the “department of orthopedics,” between October 2020 and November 2022. The hospital records, images, operation notes, and follow-up records were reviewed and analyzed. Thirty patients of cervical monoradiculopathy were investigated. All the patients who have satisfying inclusion criteria in the study period from October 2020 to November 2022 were included in the study. Patients of any age group and both the sexes and who were operated for PCF were considered. Those patients were then meticulously subjected to thorough inspection, with the help of hospital records, images, and operation notes and interviews. All the details of the patients were obtained based on previous hospital records and interactions with them and through neck disability index (NDI) score. Discussion: Decompression of the nerve root can be done by either anterior or posterior approach. Anterior approach carries risk of damaging oesophagus, trachea, carotid sheath and recurrent laryngeal nerve posterior approach includes foraminotomy in form of drilling some part of facet joint and adjacent lamina, disc can also be removed in selected cases this approach do not carry much risk. Many comparative studies shows equal beneficial outcome of pcf (posterior cervical foraminotomy)as compared to acdf (anterior cervical disectomy with fusion). Results: When we analyzed the NDI scores at different intervals there has been a positive trend showing the improvement in overall well being of an individual patient and this has resulted in major porting of the patients that has been taken as a sample has returned to there normal day to day living which they used to have earlier, before suffering from cervical radiculopathy. Conclusion: The final conclusion that can be drawn after analyzing the NDI score at different interval of time i-e before surgery, immediately and after surgery, 6 weeks post surgery, 3 months post surgery and 6 months post surgey is that patients have shown successive improvements with every follow up done.